Properties of calcium channels in guinea-pig gastric myocytes. - Katzka, D A (1989)
1. The inward membrane current in enzymatically dispersed guinea-pig gastric myocytes was studied using whole-cell voltage clamp technique. 2. Only one inward membrane current was found in gastric myocytes which was identified as the Ca2+ current based on its inhibition by Ni2+, Cd2+ and Co2+, its dependence on [Ca2+]o, and its insensitivity to variations of [Na+]o. 3. Ca2+ current activated at -20 mV, peaked around +10 mV and was markedly enhanced when the holding potential was increased from -40 to -90 mV. The enhancement of ICa at negative holding potentials did not alter the activation threshold of ICa. When Ba2+ was substituted for Ca2+, IBa was similarly enhanced at more negative potentials. 4. In cells where internal Ca2+ was buffered with 10 mM-EGTA, the time course of inactivation was fitted with two exponentials, with time constants: tau f = 53.4 +/- 18.1 ms and tau s = 175.2 +/- 46.1 ms. When Ba2+ was the charge carrier through the channel, the time course of inactivation could be fitted often by only one exponential which approximated tau s for inactivation of ICa. The voltage dependence of steady-state inactivation of Ca2+ channels was not significantly altered when Ba2+ was the charge carrier. 5. Using different buffering systems (EGTA, EDTA and citrate), we found that citrate maintained the ICa and slowed inactivation more effectively than the other buffers tested. Because the calculated change in [Ca2+]i did not differ significantly between buffer systems, we speculate that suppression of inactivation by citrate is related to increased accessability of the buffer to cytoplasmic Ca2+ near the Ca2+ channel. Changes in [Mg2+]i affected peak ICa but not the kinetics of inactivation indicating that [Mg2+]i may regulate the steady-state inactivation or the availability of the Ca2+ channels. 6. The divalent selectivity of the Ca2+ channel had the following sequence: Ba2+ greater than Ca2+ greater than or equal to Sr2+ much greater than Mg2+. In very low extracellular Ca2+ (less than 10(-7) M), the Ca2+ channel conducted Na+. 7. Increasing [H+]o appeared to differentially affect peak and maintained components of ICa. At pH less than 6.5, the maintained component of ICa was suppressed more than the peak component indicating possible time- and voltage-dependent inhibition of ICa by protons. 8. Nifedipine, D600 and diltiazem inhibited ICa in a voltage-dependent manner. The order of potency for inhibition of peak ICa was nifedipine approximately D600 much greater than diltiazem.(ABSTRACT TRUNCATED AT 400 WORDS)